Elevated triglyceride-glucose index is a risk factor for cardiovascular events in adults with type 1 diabetes: a cohort study - Rosa Oh; Seohyun Kim; Sang Ho Park; Myunghwa Jang; So Hyun Cho; Ji Yoon Kim; You-Bin Lee; Sang-Man Jin; Kyu Yeon Hur; Gyuri Kim; Jae Hyeon Kim (Cardiovascular Diabetology)
Abstract Background The triglyceride-glucose (TyG) index is recognized as an indicator of insulin resistance and is linked to cardiovascular disease (CVD) in patients with type 2 diabetes. However, its utility in patients with Type 1 diabetes (T1DM) has not been studied. Methods In this nationwide cohort study, we enrolled 14,543 patients with T1DM between 2009 and 2015, with a median follow-up duration of 7.52 years. The primary outcome was the incidence of CVD, including myocardial infarction, ischemic stroke, and heart failure. The secondary outcome was the all-cause mortality. The risk of CVD across the TyG index quartiles was compared using the Cox proportional hazards model. Results The cut-off points for the TyG quartiles were 8.46, 9.03, and 9.60. Patients in the highest TyG quartile exhibited a higher burden of cardiometabolic risk factors, including obesity, hypertension, dyslipidemia, and lower HDL cholesterol levels. Compared to the lowest quartile, the highest TyG quartile group showed a significantly increased risk of CVD (Composite CVD: adjusted hazard ratio [aHR] = 1.80; 95% confidence interval [CI] = 1.62–2.00, myocardial infarction: aHR = 1.70;95% CI = 1.38–2.10, ischemic stroke: aHR = 2.11; 95% CI = 1.78–2.50, heart failure: aHR = 1.65, 95% CI = 1.45–1.88) and all-cause mortality (aHR = 1.60, 95% CI = 1.41–1.81). Conclusions A higher TyG index was significantly associated with an increased risk of CVD and all-cause mortality in patients with T1DM. Research insights What is currently known about this topic? 1. The TyG index is associated with insulin resistance and cardiovascular disease in both patients with type 2 diabetes and the general population. What is the key research question? 1. Could the TyG index also be utilized to assess insulin resistance and cardiovascular disease risk in patients with type 1 diabetes? What is new? 1. In patients with type 1 diabetes, those in the higher TyG quartile showed a higher prevalence of metabolic dysfunction such as obesity, hypertension and dyslipidemia. 2. A higher TyG index in patients with type 1 diabetes was associated with an increased risk of all-cause mortality and cardiovascular disease including myocardial infarction, heart failure and stroke. How might this study influence clinical practice? 1. The TyG index, a simple and non-invasive marker composed of triglycerides and fasting glucose, could be used to identify patients with type 1 diabetes who have high insulin resistance and cardiovascular disease risk.